Scale-up of antiretroviral treatment access among people living with HIV in Rivers State, Nigeria, 2019–2020. (1st June 2021) - Boyd, Andrew T.; Ogbanufe, Obinna; Onyenuobi, Chibuzor; Mgbakor, Ifunanya; Bachanas, Pamela; Olupitan, Olayemi; Umeh, Clifford; Adegboye, Adeoye; Owhonda, Golden; Odafe, Solomon; Jahun, Ibrahim; Dakum, Patrick; et al.
Abstract : Objective: The aim of this study was to describe and evaluate the impact of the programme intervention of the Rivers State Antiretroviral Treatment (ART) Surge, a collaboration between the US President's Emergency Plan for AIDS Relief (PEPFAR) and the State Ministry of Health, to increase HIV case-finding and ART access in Rivers State, the state with the largest ART gap among people living with HIV (PWH) in Nigeria. Design: During April 2019−September 2020, the intervention included six specific strategies: using local government area-level ART gap analysis to guide case-finding; expanding targeted community testing; tailoring comprehensive key population HIV services; engaging HIV treatment programme stakeholders; synchronizing team efforts; and using near real-time data for programme action. Methods: Weekly reported facility and community data on tests conducted, PWH diagnosed, and PWH initiated on ART were aggregated. The total number of PWH maintained on ART was reported quarterly. Results: During May 2019−September 2020, the weekly number of newly diagnosed PWH initiated on ART supported by PEPFAR in Rivers State increased from 82 to 1723. During October 2019−September 2020, the monthly number of people screened for HIV testing eligibility in the community increased from 44 000 to 360 000. During April 2019−September 2020, the total number of PWH on ART supported by PEPFAR statewide increased by 3.8 times, from 26 041 to 99 733. Conclusion: The strategies applied by HIV program stakeholders contributed to scale-up of PWH identification and ART linkage within the Rivers State ART Surge. Continued gains through time indicate the importance of the application of a quality improvement approach to maintain programme flexibility and effectiveness. Abstract : Supplemental Digital Content is available in the text